Myasthenia Gravis and Large Granular Lymphocytic Leukemia: a rare association. (2020) - Zhang, Yumeng; Varnadoe, Christa; Tandon, Ankita; Forsyth, Peter; Komrokji, Rami; Sokol, Lubomir
Abstract: Myasthenia gravis (MG) is an autoimmune neuromuscular junction disorder sometimes observed in hematologic malignancies as a paraneoplastic syndrome. T-cell Large Granular Lymphocytic Leukemia (T-LGLL) is a rare lymphoproliferative clonal frequently associated with autoimmune disorders. Here we report two patients with T-LGLL who developed MG. In both patients the MG was bulbar without generalized weakness and did not involve the thymus. The treatment of T-LGLL led to the resolution of MG symptoms and decrease in acetylcholine receptor antibody titers in both patients suggesting a causative association.